Vascular CT Angiography Manual - Pelberg, Robert; Mazur, Wojciech; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
Vascular medicine is an ever changing and rapidly advancing field, and with the onset of state of the art diagnostic and imaging modalities, we are recognizing that vascular illness is more prevalent than once thought. The proper diagnosis and treatment of this vascular illness may prevent stroke, salvage a limb and even save a life. Advancements in CT angiography have made vascular CT angiography the modality of choice for accurately diagnosing vascular disease and the management of its treatment. Modern, multi-slice CT provides noninvasive, direct imaging of virtually the entire vascular system in a safe, effective and accurate manner without the inherent risk attributed to invasive angiography. Furthermore, it is widely available, even in institutions that do not perform invasive angiography. Vascular CT Angiography Manual distills vascular CT angiography and the diseases for which it is meant to diagnose into an easy to follow and inclusive resource. Designed for residents and fellows in cardiovascular medicine and radiology as well as for those already in practice, this work makes 'difficult to understand' concepts easy to comprehend with the aid of simple, intuitive diagrams, charts and clinical CT image examples. For those already proficient in vascular CT, this book will serve as a valuable resource as it compiles a complete radiation review, imaging protocols, screening recommendations, disease states and imaging tips in one location. It is organized and easy to follow, as each clinical chapter is organized to include sections on anatomy, disease states, accuracy of CT, and an approach to reading CT angiography.
Keywords: Medicine; Radiology, Medical; Internal medicine; Cardiology; Heart -- Surgery; Vascular Surgery; Medicine & Public Health; Cardiology; Imaging / Radiology; Diagnostic Radiology; Cardiac Surgery; Vascular Surgery; Internal Medicine